The Role of Managerial Skills on the Performance of Small and Medium Enterprise (SMES) in Jabi District, Abuja, Nigeria - Marcus Garvey Orji; Akhimien Emmanuel; Chika Margret-Mary Egwuatu (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
The objective of this study was to access the role of managerial skills on SME performance in Jabi District, Abuja, Nigeria. The study is a survey research, sampling the opinion of 240 business owners in the District. Their opinion was collected using a structured questionnaire and data collected were analyzed by tabulation, percentages and the formulated hypotheses tested using Kendall coefficient of concordance. The study discovered that these managerial skills: technical skills, conceptual skills, interpersonal relation skills, and budgeting skills had a substantial effect on the performance of SMEs. The study concluded that insufficient managerial skills are factors militating against SME performance and recommended among others that SME managers should try to understand, lead, change and regulate the behavior of the individuals and organization they manages to achieve greater performance; the government, Non-Governmental Organizations, and SME owners' unions provide adequate training.